The discovery of physical properties of food waste in composting process. - Abu Samah, Mohd Armi; Abdul Rahman, Muhammad Firdaus; Abd Halim, Khairul Bariyyah; Khan Chowdhury, Ahmed Jalal (Science Publishing Corporation Inc, 2018)
Composting as a method of solid waste management should be given attention. It gives means of producing a valuable end product, by treating of organic wastes in an environmentally friendly method which does not release any hazardous chemical which can affect human health without causing a major disruption to the surrounding ecosystem. Nevertheless, the issue of time-consuming arises and this correspond to the sink of market demand. The optimized pre-composting process was done through drying, grinding and controlled aeration resulted in the fast-compost formation and cost-effective. This study aimed to discover the physical properties of food waste in composting process. The controlled parameter of the composting which is aeration time where pre-composting processes applied was drying and grinding. The manipulated parameter of composting process happened within two durations: rotation and rest. Each container has been rotated for 15 minutes yet different resting time was applied which are 15, 25, 50, 150 minutes namely A, B, C and D. The data collection has been done in hourly basis for the total of 72 hours. Based on the statistical analysis, results show that mass reduction of samples (A=38.6%, B=32.6%, C=24.6%, D=22.6%). The compost temperature ranged between (23°C - 39°C) while the compost pH was (5.12 – 5.85). Peak level of surrounding temperature was (35.7°C) while surrounding relative humidity (53%) in normal condition. Among the highest moisture content was (52.63%) while the lowest discovered in sample D (24.81%) respectively. Results show that with the longer the aeration time, the better physical properties of compost formed. The obtained data will provide evidence on its significances application to the agencies, the public and the industrial player to cope up with this major environmental threat. This study found a significant relationship between physical factors and compost formation which contribute to better analysis, especially to food waste management.